Lupus miliaris disseminatus faciei: An uncommon dermatologic entity - Anjali Madan; Vineet Rehlan; Vijay Kumar Garg; Nidhi Mahajan (Wolters Kluwer Medknow Publications, 2017)
Lupus miliaris disseminatus faciei (LMDF) first described in 1878 is an uncommon dermatosis of unknown etiology with characteristic clinicopathological features. It mainly affecting the central area of the face showing a characteristic tendency to involve the lower eyelids. Various treatments have been tried with tetracyclines, isotretinoin, dapsone, prednisolone, clofazimine, isoniazid and corticosteroids, with variable results. We present the case of a 30 year old patient with characteristic complaints of eruption of multiple, discrete reddish raised asymptomatic lesion all over face with histopathology suggestive of Lupus miliaris disseminatus faciei